Microcellular hemp fibre reinforced polypropylene matrix composites - TAŞDEMİR, MÜNİR (My University, 2022)
Microcellular nature fiber reinforced polymer materials have significant application especially automotive industry because of their advantages such as their reducing weight and improving strength of components through microcellular structure, process and product. This research investigates chemical foaming agent types and their contents (1-2-3%wt.) impacts on physical properties of hemp fibre reinforced PP composites. Water absorption test, melt flow index test (MFI), density, Vicat softening temperature, heat deflection temperature (HDT), water absorption test would done. The morphology of the microcellular hemp fibre composites were examined using scanning electron microscopy (SEM) to observed cell morphology cell size, shape, and distribution of cells account for physical properties behavior.
Keywords: Chemical Foaming Agent; Hemp Fibre; Microcellular Composites; Natural Fiber; Plastic İnjection.